Aetiology and outcome of acute diarrhoea in children with severe acute malnutrition: a comparative study. Issue 9 (8th June 2020) - Jain, Abhishek; Shah, Dheeraj; Das, Shukla; Saha, Rumpa; Gupta, Piyush
Abstract: Objective: To compare the microbiological profile, clinical course and outcome of acute diarrhoea in children aged <5 years having severe acute malnutrition (SAM) with those of children having normal nutritional status. Design: Cross-sectional comparative study. Setting: Tertiary-care hospital catering mainly to the urban poor of East Delhi, India. Participants: Children aged <5 years ( n 140; seventy with SAM (cases) and seventy with normal anthropometry (controls)) with acute diarrhoea (duration < 14 d). Stool samples were collected for conventional culture, microscopy, acid-fast staining, rotavirus and Cryptosporidium antigen detection, and subtyping of diarrhoeagenic Escherichia coli (DEC). We followed-up these children for persistent diarrhoea and subsequent diarrhoeal episode in the next 3 months. Results: Rotavirus was detected in six (9 %) cases and in fifteen (21 %) controls ( P = 0·03; OR = 0·34; 95 % CI 0·12, 0·94). DEC was isolated significantly more in cases compared with controls (93 v . 64 %; P < 0·001; OR = 7·25; 95 % CI 2·57, 20·4). Cryptosporidium was detected in seven (10 %) cases and five (7 %) controls. Total duration of diarrhoea and percentage change in weight after resolution of diarrhoea were comparable between cases and controls. At 3-month follow-up, number of subsequent episodes of diarrhoea and persistent diarrhoea were comparable between the two groups. Conclusions: Rotavirus was found significantly less frequently, whereas DEC was detected more frequently in children with SAM in comparison to non-malnourished children. To further reduce diarrhoea-related mortality, preventive and therapeutic interventions need to be designed against organisms causing diarrhoea in children with SAM.